The effectiveness of oral protein supplementation in malnourished peritoneal dialysis patients - Usta, Mehmet; Ersoy, Alparslan; Ayar, Yavuz (The European Research Journal, 2021)
Objectives: Malnutrition is a common problem in chronic renal disease patients during pre-dialysis and dialysis, leading to increased cardiovascular diseases and mortality. This study aimed to evaluate the efficacy of supplemental protein supplementation on malnutrition in peritoneal dialysis patients. Methods: Eighty-four stable adult peritoneal dialysis patients included in this study. In addition to the standard diets, oral nutritional product (372 calories, 61 g protein, 30 g glutamine, and 30 g arginine/100 g powder sachet twice a day) gave to patients. Before the study and after three months from the supportive therapy; anthropometric measurements with serum urea, creatinine, total protein, albumin, cholesterol, KtV, body mass index was analyzed. Results: The mean age of peritoneal dialysis patients was 60 (46-78) years. Serum urea levels from 96 ± 44 to 109 ± 42 mg/dL (p = 0.007), total protein levels from 5.85 ± 0.68 to 6.18 ± 0.66 g/dL (7.8%, p = 0.007), albumin levels increased from 3.02 ± 0.27 to 3.32 ± 0.34 g/dL (11.7%, p = 0.003) increased significantly after an average of 0.43 g/kg protein and 178 cal/day energy support. Conclusions: Albumin is an indicator of malnutrition related mortality. Therefore, using of protein nutritional products in addition to standard treatment may be beneficial for malnourished peritoneal dialysis patients.